Visible-light-responsive photocatalytic nano composite material and preparation method thereof
By combining nano-silver vanadate with Bi2MoO6 and building a nano-heterojunction, the limitations of traditional semiconductor photocatalysts in terms of visible light response are solved, and a wider visible light response and higher photocatalytic performance are achieved.
Patent Information
- Application Number
- CN202510184831.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-04-25
AI Technical Summary
Traditional semiconductor photocatalysts can only absorb ultraviolet light, limiting their performance in practical applications, especially in terms of visible light response.
By compounding nano-silver vanadate (AgVO3) with Bi2MoO6, Bi2MoO3 nanoheterojunction was constructed, and the composite material was prepared by solvothermal method to broaden its visible light response range and accelerate the separation of photogenerated electron-holes.
The visible light response range of photocatalytic materials has been significantly broadened, the photocatalytic performance has been improved, and the photocatalytic activity has been higher under visible light conditions.
Smart Images

Figure CN119869624A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photocatalytic composite materials, and particularly relates to a visible light responsive photocatalytic nanocomposite material and a preparation method thereof. Background Art
[0002] Photocatalysis is an environmentally friendly and promising technology for treating organic pollutants with high energy efficiency. The most important thing in the photocatalytic reaction process is the photocatalytic material used, and the most commonly used is semiconductor material. The disadvantage is that traditional semiconductor photocatalysts can only absorb ultraviolet light (about 4% of solar energy), which seriously limits the practical application of semiconductor photocatalysis. Therefore, it is particularly important to develop new semiconductor photocatalysts that respond to visible light (about 45% of solar energy). 2 MoO 6 ) is a green and environmentally friendly material with the simplest structure in the Olivieris family, excellent thermal stability, good dispersibility in solvents, self-nontoxicity, and high visible light response performance. It has great potential in solving environmental problems.
[0003] However, the visible light response range of pure bismuth molybdate materials is relatively limited, which limits the performance of its photocatalytic performance. The semiconductor composite technology of constructing nano-heterojunction is one of the most commonly used and effective methods to broaden the visible light response range of photocatalytic materials and improve photocatalytic performance. Composite semiconductor photocatalytic materials refer to composite particles formed by combining two or more semiconductors in some way. After the material is composited, the structure or properties change, and new properties that single-phase materials do not have are often produced. Different semiconductors have different energy band structures, and after they are composited, they can separate photogenerated electrons and holes more effectively. Therefore, the prerequisite for different semiconductors to be composited is whether the energy levels between the materials match, so as to improve the absorption efficiency of visible light, better separate photogenerated electrons and holes, and enhance the photocatalytic performance. Summary of the invention
[0004] In view of the problems of the prior art, the present invention provides a visible light responsive photocatalytic nanocomposite material and a preparation method thereof. The present invention adopts nano silver vanadate (AgVO 3 ) and Bi 2 MoO 6 The compound was prepared by solvothermal method to obtain Bi 2 MoO 6 / AgVO 3 Composite materials, by constructing Bi 2 MoO 6 / AgVO 3Nanoheterojunction accelerates the separation of photogenerated electron-hole pairs and, on the other hand, broadens the visible light response range of photocatalytic materials, thereby improving the photocatalytic performance of the materials.
[0005] The technical solution adopted by the present invention is as follows: a visible light responsive photocatalytic nanocomposite material, which is Bi 2 MoO 6 / AgVO 3 Composite materials, including AgVO 3 As carrier, Bi 2 MoO 6 To form AgVO 3 Attachments on.
[0006] Further, forming the Bi 2 MoO 6 / AgVO 3 AgVO in composites 3 The raw materials used include soluble silver salt and vanadate to form the Bi 2 MoO 6 / AgVO 3 Bi in composite materials 2 MoO 6 The raw materials used include bismuthate and molybdate.
[0007] Furthermore, the Bi 2 MoO 6 / AgVO 3 AgVO in composite materials 3 The mass fraction of is 70wt% to 95wt%, preferably 85wt%.
[0008] A method for preparing a photocatalytic nanocomposite material, comprising:
[0009] Step 1, obtain AgVO 3 Nanoribbons;
[0010] Step 2, synthesis of Bi 2 MoO 6 / AgVO 3 Nanocomposites:
[0011] Step 2.1: Obtained AgVO 3 The nanobelts are dispersed in an organic solvent, and bismuthate is dissolved in the AgVO nanobelts. 3 In the organic solvent of the nanobelts, solution A is obtained; in which bismuthate accounts for 1% of AgVO 3 The mass percentage of the nanoribbons is 8-48wt%, preferably 24%;
[0012] Step 2.2, dissolving molybdate in the same organic solvent to obtain solution B;
[0013] Step 2.3, solution A and solution B are mixed, wherein the molar ratio of molybdate to bismuthate is 1:(1.5-2.5), preferably 1:2. The mixture is fully reacted under heating conditions to make AgVO 3 Nanoribbons as carriers, Bi 2 MoO 6 Crystal nuclei grow on AgVO 3 The surface of the nanobelt was cooled to room temperature, washed and dried to obtain Bi 2 MoO 6 / AgVO 3 Composite materials.
[0014] Since molybdate and bismuthate generate Bi 2 MoO 6 The process is more complicated and side reactions may occur, that is, the raw materials cannot all generate Bi 2 MoO 6 , there is a certain loss, therefore, under ideal conditions, the molar ratio of molybdate to bismuthate is 1:2.
[0015] Furthermore, in step 2.3, the reaction conditions are: reaction at 130° C. to 180° C. in a closed container for 5 h to 24 h.
[0016] Furthermore, in step 2.3, the drying is carried out by oven drying or freeze drying, the oven drying conditions are a temperature of 50 to 80°C and a time of 5 to 10 hours, and the freeze drying conditions are freeze drying at -80°C to -20°C for 8 to 15 hours.
[0017] Furthermore, the organic solvent used in step 2.1 is an alcohol organic compound.
[0018] Further, the specific process of step 1 is:
[0019] Step 1.1, AgNO 3 The aqueous solution was added dropwise to the NH 4 VO 3 In aqueous solution, adjust the pH of the mixture to neutral, and then stir thoroughly in the dark;
[0020] Step 1.2, fully react under heating conditions, cool to room temperature, filter, wash, and dry to obtain AgVO 3 Nanoribbons.
[0021] Furthermore, in step 1.1, AgNO 3 The aqueous solution was added dropwise to NH 4 VO 3 Magnetic stirring is used for aqueous solutions. Magnetic stirring accelerates dissolution and makes the solution uniform.
[0022] AgNO 3 and NH 4 VO 3 The reaction equation is as follows:
[0023] NH 4 VO 3 +AgNO 3 =AgVO 3 ↓+NH 3 ↑+HNO 3 .
[0024] Furthermore, in step 1.2, ultrapure water is added before the reaction to provide more solvents and a larger space for the reaction.
[0025] Furthermore, the reaction conditions of step 1.2 are 150° C. to 200° C. and reaction time in a closed container for 12 h to 36 h.
[0026] Furthermore, in step 1.2, the drying is carried out by drying or freeze drying, the drying conditions are 50-80°C for 5-10 hours, and the freeze drying conditions are freeze drying at -80°C to -20°C for 8-15 hours. When freeze drying is used, the temperature is relatively low, which effectively avoids adverse side reactions and can maintain the activity and stability of the compound.
[0027] Furthermore, in step 1.2, a microporous filter membrane is used for suction filtration. This is mainly to filter out the supernatant and obtain AgVO 3 precipitation.
[0028] Furthermore, AgVO 3 Ultrasonic dispersion is used when nanobelts are dispersed in organic solvents. Ultrasonic dispersion can make micro-nano materials disperse more evenly.
[0029] The invention has the following beneficial effects: The invention discloses a visible light responsive photocatalytic nanocomposite material and a preparation method thereof, using nano silver vanadate (AgVO) having good visible light catalytic activity and environmentally friendly properties. 3 ) and Bi 2 MoO 6 The compound was prepared by solvothermal method to obtain Bi 2 MoO 6 / AgVO 3 Composite materials, by constructing Bi 2 MoO 6 / AgVO 3 Nanoheterojunction accelerates the separation of photogenerated electron-hole pairs and, on the other hand, broadens the visible light response range of photocatalytic materials, thereby improving the photocatalytic performance of the materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 for Bi 2 MoO 6 / AgVO 3 Schematic diagram of the preparation method of the composite material
[0031] Figure 2 for Bi 2 MoO 6 Nanosheets and Bi 2 MoO 6 / AgVO 3 XRD patterns of composite materials;
[0032] Figure 3 for Bi 2 MoO 6 / AgVO 3 Scanning electron microscopy and energy spectrum of the composite material;
[0033] Figure 4 for Bi 2 MoO 6 / AgVO 3 Transmission electron microscope images of composite materials;
[0034] Figure 5 for Bi 2 MoO 6 / AgVO 3 UV-visible diffuse reflectance absorption spectrum of the composite material;
[0035] Figure 6 This is a diagram showing the effect of photocatalytic degradation of Rhodamine B. DETAILED DESCRIPTION
[0036] The following is an explanation and description of the technical solutions of the embodiments of the present invention in conjunction with the accompanying drawings of the present invention, but the following embodiments are only preferred embodiments of the present invention, not all. Based on the embodiments in the implementation mode, other embodiments obtained by those skilled in the art without creative work are all within the protection scope of the present invention.
[0037] Example 1
[0038] Weigh 1 mmol NH 4 VO 3 Dissolve it in 30 mL ultrapure water, heat and stir continuously to make it completely dissolved, then add 30 mL containing 1 mmol AgNO 3 The solution was added dropwise to NH 4 VO 3The solution was added, and the pH value of the mixture was adjusted to 7. Stirring was continued for 5 hours at room temperature in the dark. After stirring, the suspension was transferred to a 100 mL polytetrafluoroethylene high-pressure reactor, and ultrapure water was added to make the filling degree reach 80%. When the reactor was used, the solution could not exceed 80% of the volume to avoid the risk of explosion. The reactor was placed in an oven and reacted at 180°C for 24 hours. After cooling to room temperature, the product was filtered on a microporous filter membrane with a pore size of 0.22 μm. The product was washed several times with ultrapure water and anhydrous ethanol respectively. The treated material was placed in a freeze dryer and freeze-dried at -80°C for 8 hours to obtain AgVO. 3 Nanoribbons.
[0039] As attached Figure 1 As shown, the synthesized AgVO 3 The nanobelts were washed repeatedly with deionized water and centrifuged for more than three times. After washing and drying, 1 g of AgVO 3 The nanobelts were ultrasonically dispersed in 5 mL of ethylene glycol, followed by the addition of 280 mg of Bi(NO 3 ) 3 ·5H 2 O, stirring to make Bi(NO 3 ) 3 ·5H 2 O dissolved to form solution A. In 5 mL of ethylene glycol, 70 mg of Na 2 MoO 4 ·2H 2 O, stirred until dissolved to form solution B, then mixed solution A and solution B and stirred for 30 minutes. Add 20 mL of ethanol to the mixed solution, continue stirring for 30 minutes, transfer the mixed solution into a 45 mL polytetrafluoroethylene autoclave, and react at 160°C for 10 hours. After cooling naturally to room temperature, wash with water and ethanol three times each, place the treated material in a freeze dryer, freeze dry at -80°C for 8 hours, and finally obtain Bi 2 MoO 6 / AgVO 3 Composite materials. The polytetrafluoroethylene reactor has a certain closed space and can provide a certain pressure during the reaction.
[0040] Figure 2 The red curve is Bi 2 MoO 6 The XRD spectrum of the nanosheets shows that the diffraction peaks at 2θ of 28.16°, 32.46°, 35.94°, 46.98°, 55.58° and 58.18° correspond to the (131), (200), (151), (062), (331) and (262) crystal planes, respectively, which are consistent with the orthorhombic Bi 2 MoO 6The PDF standard card (JCPDS No.84) is consistent with the . Figure 2 The blue curve is AgVO 3 -Bi 2 MoO 6 The XRD spectrum of the composite material has roughly the same diffraction peak position as the pure diffraction peak position, but AgVO appears at 30.86° 3 Diffraction peaks, which correspond to monoclinic AgVO 3 No other diffraction peaks were found, indicating that the obtained AgVO 3 -Bi 2 MoO 6 AgVO exists in the composite material 3 .
[0041] Figure 3 A and B in the equation are both Bi 2 MoO 6 / AgVO 3 SEM photos of composite materials show that Bi 2 MoO 6 Nanosheets tightly wrapped in AgVO 3 The surface of the composite material is about several hundred nanometers to several microns in diameter. Figure 3 C and D in the figure are the results of X-ray energy spectrum analysis of the composite material, indicating that the composite material is mainly composed of five elements, Bi, Mo, Ag, V, and O, and is evenly distributed.
[0042] Transmission electron microscopy was used to further observe Bi 2 MoO 6 / AgVO 3 The morphology of the composite material. Figure 4 As shown, Bi 2 MoO 6 / AgVO 3 The composite material is in the shape of a ribbon with a diameter of about 500nm. 2 MoO 6 Nanosheets tightly wrapped in AgVO 3 The surface of the nanoribbons demonstrates the successful composite of the two materials.
[0043] The light absorption properties of materials can be characterized by UV-visible absorption spectroscopy, such as Figure 5 It can be seen that nano Bi 2 MoO 6 and Bi 2 MoO 6 / AgVO 3 The composite material has strong absorption in both the ultraviolet and visible light regions, showing good visible light absorption performance.2 MoO 6 The maximum absorption edge of Bi is about 480nm, while 2 MoO 6 / AgVO 3 The maximum absorption edge of the composite material can reach about 536nm. The bandgap width Eg of the crystalline semiconductor can be calculated by the formula Eg = 1240 / λg, combined with the absorption spectrum, to obtain nano Bi 2 MoO 6 and Bi 2 MoO 6 / AgVO 3 The Eg of the composites are 2.58eV and 2.31eV respectively. 3 Compare 2 MoO 6 The composite modification of nano Bi 2 MoO 6 The visible light absorption range is significantly improved, which makes it have potential application prospects in visible light catalysis.
[0044] The aqueous solution of organic dye Rhodamine B (RhB) is quite stable to visible light excitation. RhB is used as a simulated pollutant to evaluate the photocatalytic performance of photocatalytic materials. The schematic diagram of the experimental device for photocatalytic degradation of Rhodamine B is shown in Figure 6 As shown in A. Test of the photocatalytic performance and rate constant of the material: 50 mg of nano-photocatalytic composite material and 10 mL of rhodamine B (1×10 - 4 mol / L) solution was added to a reaction glass bottle, and the mixture was placed in a dark place (completely protected from light) and magnetically stirred for 60 minutes to reach adsorption-desorption equilibrium. Then a 300W xenon lamp was used as the light source for photocatalytic degradation, and observation was performed every 20 minutes until the Rhodamine B solution was completely degraded to colorless, and the final fading time was recorded. The time-concentration change curve of photocatalytic degradation of RhB is shown in the figure Figure 6 As shown in B, the results show that when the photocatalysis is carried out for 20 minutes, pure Bi 2 MoO 6 The degradation rate of RhB nanosheets was 30%, and Bi 2 MoO 6 / AgVO 3 The degradation rate of RhB in the composite material was 80%. When the photocatalysis was carried out for 60 min, the degradation rate of pure Bi 2 MoO 6 The degradation rate of RhB nanosheets was 50%, while that of Bi 2 MoO 6 / AgVO 3The RhB treated with the composite material was almost completely degraded. This proves that the semiconductor composite heterojunction method can significantly improve the Bi 2 MoO 6 The excellent photocatalytic performance makes it have potential application prospects in visible light catalysis.
[0045] Example 2
[0046] The difference between this embodiment and embodiment 1 is that: Bi(NO 3 ) 3 ·5H 2 O added in an amount of 100 mg, Na 2 MoO 4 ·2H 2 O was added in an amount of 20 mg, that is, the molar ratio of molybdate to bismuthate was 1:2.5 to prepare AgVO 3 The nanobelts were reacted at 150°C for 36 hours, and the drying conditions were the same as those in Example 1; the A and B solutions were mixed and reacted at 130°C for 24 hours, then washed and dried at 80°C for 5 hours. 2 MoO 6 / AgVO 3 AgVO in composite materials 3 The mass percentage is 95%.
[0047] Example 3
[0048] The difference between this embodiment and embodiment 1 is that: Bi(NO 3 ) 3 ·5H 2 O added in an amount of 130 mg, Na 2 MoO 4 ·2H 2 O was added in an amount of 40 mg, that is, the molar ratio of molybdate to bismuthate was 1:1.5 to prepare AgVO 3 The reaction conditions for the nanobelts were the same as those in Example 1, and freeze-dried at -20°C for 15 h; the A and B solutions were mixed and reacted at 180°C for 5 h, then washed and dried at 50°C for 10 h. The formed Bi 2 MoO 6 / AgVO 3 AgVO in composite materials 3 The quality fraction is 90%.
[0049] Example 4
[0050] The difference between this embodiment and embodiment 2 is that: Bi(NO 3 ) 3 ·5H 2 O added in an amount of 400 mg, Na 2MoO 4 ·2H 2 O was added in an amount of 100 mg, that is, the molar ratio of molybdate to bismuthate was 1:2, and AgVO was prepared. 3 The reaction conditions and drying method for the nanobelts were the same as those in Example 2. Solutions A and B were mixed and reacted at 180°C for 5 h, then washed and freeze-dried at -80°C for 15 h. 2 MoO 6 / AgVO 3 AgVO in composite materials 3 The mass fraction is 80%.
[0051] Example 5
[0052] The difference between this embodiment and embodiment 2 is that: Bi(NO 3 ) 3 ·5H 2 O added in an amount of 400 mg, Na 2 MoO 4 ·2H 2 O was added in an amount of 130 mg, that is, the molar ratio of molybdate to bismuthate was 1:1.5 to prepare AgVO 3 The reaction conditions for the nanobelts were the same as those in Example 2, and the solution was dried at 80°C for 8 h. After the A and B solutions were mixed and reacted (the reaction conditions were the same as those in Example 2), the solution was freeze-dried at -20°C for 8 h. 2 MoO 6 / AgVO 3 AgVO in composite materials 3 The mass fraction is 75%.
[0053] Example 6
[0054] The difference between this embodiment and embodiment 3 is that: Bi(NO 3 ) 3 ·5H 2 O added in an amount of 510 mg, Na 2 MoO 4 ·2H 2 O was added in an amount of 170 mg, that is, the molar ratio of molybdate to bismuthate was 1:1.5, and AgVO was prepared. 3 The reaction conditions for the nanobelts were 200°C for 12 h, drying at 50°C for 10 h, mixing of the A and B solutions (the reaction conditions were the same as those in Example 2), and freeze drying at -20°C for 8 h. 2 MoO 6 / AgVO 3 AgVO in composite materials 3 The mass fraction is 70%.
[0055] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that the present invention includes but is not limited to the contents described in the drawings and the above specific embodiments. Any modification that does not deviate from the functional and structural principles of the present invention will be included in the scope of the claims.
Claims
1. A visible light responsive photocatalytic nanocomposite material, characterized in that: It is a Bi2MoO6 / AgVO3 composite material, wherein AgVO3 is a carrier and Bi2MoO6 is an attachment formed on AgVO3.
2. The visible light responsive photocatalytic nanocomposite material according to claim 1, characterized in that: The raw materials used to form AgVO3 in the Bi2MoO6 / AgVO3 composite material include soluble silver salt and vanadate, and the raw materials used to form Bi2MoO6 in the Bi2MoO6 / AgVO3 composite material include bismuthate and molybdate.
3. The visible light responsive photocatalytic nanocomposite material according to claim 1, characterized in that: The mass fraction of AgVO3 in the Bi2MoO6 / AgVO3 composite material is 70wt% to 95wt%.
4. A method for preparing a photocatalytic nanocomposite material, wherein the photocatalytic nanocomposite material is the visible light responsive photocatalytic nanocomposite material according to claim 1, 2 or 3, characterized in that: include: Step 1, obtaining AgVO3 nanobelts; Step 2, synthesis of Bi2MoO6 / AgVO3 nanocomposite material: Step 2.1, dispersing the obtained AgVO3 nanobelts in an organic solvent, and then dissolving bismuthate in the organic solvent containing the AgVO3 nanobelts to obtain solution A; Step 2.2, dissolving molybdate in the same organic solvent to obtain solution B; Step 2.3, mixing solution A and solution B, wherein the molar ratio of molybdate to bismuthate is 1:(1.5-2.5), and fully reacting under heating conditions so that the AgVO3 nanobelts serve as carriers and Bi2MoO6 crystal nuclei grow on the surface of the AgVO3 nanobelts. After cooling to room temperature, washing and drying are performed to obtain a Bi2MoO6 / AgVO3 composite material.
5. The method for preparing the visible light responsive photocatalytic nanocomposite material according to claim 4, characterized in that: In step 2.3, the reaction conditions are: reaction at 130° C. to 180° C. in a closed container for 5 h to 24 h.
6. The method for preparing the visible light responsive photocatalytic nanocomposite material according to claim 4, characterized in that: In step 2.3, the drying is carried out by oven drying or freeze drying, the oven drying conditions are a temperature of 50 to 80°C and a time of 5 to 10 hours, and the freeze drying conditions are freeze drying at -80°C to -20°C for 8 to 15 hours.
7. The method for preparing a visible light responsive photocatalytic nanocomposite material according to claim 4, characterized in that: The organic solvent used in step 2.1 is an alcohol organic compound.
8. The method for preparing a visible light responsive photocatalytic nanocomposite material according to claim 4, characterized in that: Step 1 Specific process: Step 1.1, add the AgNO3 aqueous solution dropwise into the NH4VO3 aqueous solution, adjust the pH of the mixture to neutral, and then stir it thoroughly in the dark; Step 1.2, react fully under heating conditions, cool to room temperature, filter, wash and dry to obtain AgVO3 nanobelts.
9. The method for preparing a visible light responsive photocatalytic nanocomposite material according to claim 8, characterized in that: The reaction conditions of step 1.2 are 150° C. to 200° C. and reaction time in a closed container for 12 h to 36 h.
10. The method for preparing a visible light responsive photocatalytic nanocomposite material according to claim 8, characterized in that: In step 1.2, the drying is carried out by oven drying or freeze drying, and the oven drying conditions are a temperature of 50 to 80° C. and a time of 5 to 10 hours, or the freeze drying conditions are freeze drying at -80° C. to -20° C. for 8 to 15 hours.
Citation Information
Cited By
AgVO3 / CuBi2O4 photocatalytic material as well as preparation method and application thereof
CN122298520A